5x+2x^2+8x+34+8x+12x=

5x+2x^2+8x+34+8x+12x=2x^2+33x+34

Question

Asked 4/8/2012 8:14:16 PM

Updated 7/16/2014 2:02:29 AM

1 Answer/Comment

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Rating

8

5x+2x^2+8x+34+8x+12x=2x^2+33x+34

Added 7/16/2014 2:02:29 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/16/2014 4:18:12 AM]

(12y3 + 9 y2 + 21y) **Weegy:** x+3y=-15
3y=-x-15
y=(-1/3)x-5 **User:** (10x2 – 14x – 12) ÷ (5x + 3) **Weegy:** x=2 **User:** (4x + 1 )(x2 – 9x + 5) **Weegy:** Best Answer - Chosen by Voters
((4/x) - (2/4x)) / ((1/2x) + (3/2x))
= ((16/4x) - (2/4x))/(4/2x)
= (14/4x)/(2/x)
= (14/4x) * (x/2)
= 14x/8x
= 14/8
= 7/4
(More)

Question

Updated 6/4/2014 8:21:17 AM

2 Answers/Comments

12y^3 + 9 y^2 + 21y = 3y(4y^2 + 3y + 7)

Added 6/4/2014 8:18:13 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/5/2014 4:12:40 AM]

(10x^2 – 14x – 12) ÷ (5x + 3)

= (5x + 3)(2x - 4)/(5x + 3)

= 2x - 4

= (5x + 3)(2x - 4)/(5x + 3)

= 2x - 4

Added 6/4/2014 8:21:09 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/5/2014 4:13:07 AM]

(5x^2 + 3x ) + ( 2x + 5) **Weegy:** First, get rid of the parentheses. 5x^2+3x+2x+5. Second, addition. 5x^2+5x+5 Third, divide everything by 5. x^2+x+5 **User:** (5x – 5 ) – ( 3x – 3) **Weegy:** please indicate what you would like to solve for or how you would like to solve this, you did not give enough information for me to do anything (More)

Question

Updated 9/18/2016 2:46:08 PM

2 Answers/Comments

(5x – 5 ) – ( 3x – 3) **Weegy:** is equal to 8x **User:** (8x – 2) + (7x + 6) **User:** (4x – 3.5) – (3x + 1.7) **Weegy:** First, get rid of the parenthese, 4x-3.5-3x-1.7 Second, Subtraction, x-5.2. x-5.2x is the answer. **User:** (12y3 + 9 y2 + 21y) ÷ 3y **Weegy:** x+3y=-15
3y=-x-15
y=(-1/3)x-5 (More)

Question

Updated 9/5/2014 4:11:57 AM

4 Answers/Comments

(5x – 5 ) – ( 3x – 3)

= (5x - 5) + (-3x + 3)

= 2x - 2

= (5x - 5) + (-3x + 3)

= 2x - 2

Added 9/5/2014 4:09:25 AM

This answer has been confirmed as correct and helpful.

(8x – 2) + (7x + 6) = 15x + 4

Added 9/5/2014 4:09:41 AM

This answer has been confirmed as correct and helpful.

(4x – 3.5) – (3x + 1.7)

= (4x - 3.5) + (-3x - 1.7)

= x - 5.2

= (4x - 3.5) + (-3x - 1.7)

= x - 5.2

Added 9/5/2014 4:10:06 AM

This answer has been confirmed as correct and helpful.

(12y^3 + 9y^2 + 21y) ÷ (3y)

= (12y^3/3y) + (9y^2/3y) + (21y/3y)

= 4y^2 + 3y + 7

= (12y^3/3y) + (9y^2/3y) + (21y/3y)

= 4y^2 + 3y + 7

Added 9/5/2014 4:11:57 AM

This answer has been confirmed as correct and helpful.

37,047,165

questions answered

There are no comments.